« Blizzard de formulaires officiels », ou la trace du mocassin à l’épreuve de la trace d’encre dans Tracks et Four Souls de Louise Erdrich - Bouzonviller, Elisabeth (ELOHI, 2013)
The links between Native Americans and nature are part of long-lived clichés. If American novelist Louise Erdrich celebrates a primeval America where indigenous people lived indeed in harmony with nature, her pastoral vision is never Manichean because individuals always behave in their own personal ways. Her Native America is definitely modern and while it denounces an ecological mess and the disappearance of indigenous cultures much attached to their natural habitats, it also rejects an ideal vision in which the Natives were part of a unspoiled setting along the “Noble savage” myth. In this article, we focus on Tracks (1988) and Four Souls (2004) and stress the various nuances of her approach of the indigenous pastoral myth. Whereas Erdrich’s fiction shows the power of attachment to a lost natural America, it also emphasizes the importance of words and memory. Thus, she does not express a form of nostalgia implying a desire for revenge for this violent dispossession due to colonization but suggests survival and resilience thanks to her wise appeal to memory through story-telling and literature. Les liens que les Indiens entretiennent avec la nature font partie des clichés longtemps ressassés. Cependant, tandis que la romancière amérindienne Louise Erdrich célèbre une certaine Amérique des origines où les peuples indigènes respectaient la nature et vivaient en harmonie avec elle, cette vision pastorale n’est pour elle jamais manichéenne car les individus ont leurs spécificités. Résolument moderne, l’Amérique autochtone d’Erdrich, dénonce un gâchis écologique et la disparition d’une culture en lien étroit avec la nature mais elle suggère aussi l’absence d’un idéal de pureté naturelle où l’Indien ferait partie du décor selon le mythe du bon sauvage. Dans cet article centré sur les romans Tracks (1988) et Four Souls (2004), nous mettons en relief son approche nuancée de la pastorale indigène. Si la fiction d’Erdrich montre la force d’un attachement à une nature disparue, elle est aussi chant de la lettre et de la ...